Agencia, conflicto y desarrollo humano en Ayacucho: el caso de Sacsamarca post Sendero Luminoso - Eskenazi, Jael (2015)
The district of Sacsamarca, located in the province of Huanca Sancos in the region of Ayacucho in Peru, was one of the most affected districts by the Internal Armed Conflict during the eighties (CAI, in Spanish). Violence, as an exogenous variable, transformed the political, economic, and social land- scape within this community, and left tremendous losses that still have not been overcome. This paper analyzes the loss of agency among Sacsamarca’s inhabitants, within a framework of social resilience. For this purpose, we examine three crucial factors that were altered by the CAI: economic, politicaland demographic.